(untitled) - Kennedy, X. J. (New York, 2003)
The rich tradition of Kennedy and Gioia's collective poetic voice brings personal warmth and a human perspective to the discussion of literature. "Writer's "Perspectives" sections give commentary on the craft of writing and revising from authors, which provide insight and a more human perspective on literature and the writing process. "Writing Critically" sections, at the end of each major chapter, expand coverage of composition with accessible and pragmatic suggestions on writing. "Critical Approaches" to Literature section provides two essays on every major school of criticism with sections on gender criticism and cultural studies. New stories, poems, drama and fiction casebooks and a glossary of literary terms have been added to the new edition. For those interested in the study and composition of literature.
Keywords: Literature; Collections